Pathways to Tailor Photocatalytic Performance of TiO(2) Thin Films Deposited by Reactive Magnetron Sputtering - Vahl, Alexander (Materials (Basel), 2019)
TiO(2) thin films are used extensively for a broad range of applications including environmental remediation, self-cleaning technologies (windows, building exteriors, and textiles), water splitting, antibacterial, and biomedical surfaces. While a broad range of methods such as wet-chemical synthesis techniques, chemical vapor deposition (CVD), and physical vapor deposition (PVD) have been developed for preparation of TiO(2) thin films, PVD techniques allow a good control of the homogeneity and thickness as well as provide a good film adhesion. On the other hand, the choice of the PVD technique enormously influences the photocatalytic performance of the TiO(2) layer to be deposited. Three important parameters play an important role on the photocatalytic performance of TiO(2) thin films: first, the different pathways in crystallization (nucleation and growth); second, anatase/rutile formation; and third, surface area at the interface to the reactants. This study aims to provide a review regarding some strategies developed by our research group in recent years to improve the photocatalytic performance of TiO(2) thin films. An innovative approach, which uses thermally induced nanocrack networks as an effective tool to enhance the photocatalytic performance of sputter deposited TiO(2) thin films, is presented. Plasmonic and non-plasmonic enhancement of photocatalytic performance by decorating TiO(2) thin films with metallic nanostructures are also briefly discussed by case studies. In addition to remediation applications, a new approach, which utilizes highly active photocatalytic TiO(2) thin film for micro- and nanostructuring, is also presented.